2011
DOI: 10.1136/bmjqs.2010.048983
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of paediatric cardiac surgical microsystems: assessing the relationships between non-routine events, teamwork and patient outcomes

Abstract: Structured observation of effective teamwork in the operating room can identify substantive deficiencies in the system and conduct of procedures, even in otherwise successful operations. High performing teams are more resilient displaying effective teamwork when operations become more difficult.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(46 citation statements)
references
References 30 publications
0
46
0
Order By: Relevance
“…They also seem to take into account the context and setting in which the observation occurs, and consider both the environmental factors as well as factors that relate to the task itself. 20 For example, attendings and residents reported that team dynamics played a large role in influencing trust decisions. We also found that attending physicians rely on indirect observation and will inquire among their colleagues and other senior residents to gain information about their trainees abilities and integrity.…”
Section: Discussionmentioning
confidence: 99%
“…They also seem to take into account the context and setting in which the observation occurs, and consider both the environmental factors as well as factors that relate to the task itself. 20 For example, attendings and residents reported that team dynamics played a large role in influencing trust decisions. We also found that attending physicians rely on indirect observation and will inquire among their colleagues and other senior residents to gain information about their trainees abilities and integrity.…”
Section: Discussionmentioning
confidence: 99%
“…. Dynamic models of adverse error causation have been suggested in high-risk surgeries by which small, seemingly innocuous events concatenate to create errors, near-misses or injuries in the operating room (de Leval et al 2000;Catchpole et al 2006;Schraagen et al 2011). .…”
Section: Surgical Safetymentioning
confidence: 99%
“…Observational and behavioural methods have been deployed to understand teamwork, socio-technical complexity, the effect of interventions, performance shaping factors and the effects on patient outcomes (Carthey 2003;Undre et al 2007;Schraagen et al 2011). .…”
Section: Surgical Safetymentioning
confidence: 99%
“…119,133 Acknowledgments: The authors wish to thank Ann Line, DVM, MS, and Russell Savage, MSA, CPA, for their assistance with data management and analysis. Other measures include the frequency of "non-routine events" 96 and "minor problems" 79 which were heterogeneous and reflected a wide range of items and multiple constructs.…”
Section: Implications For Future Research and Practicementioning
confidence: 99%